2016
DOI: 10.1007/s11999-015-4456-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Lessons From a Worldwide, Multicenter, Followup Study of the Recalled Articular Surface Replacement Hip System

Abstract: Background Adverse local tissue reactions (ALTRs) around hip arthroplasties are an important reason for failure of metal-on-metal (MoM) hip implants. Little is known about capsular dehiscence patterns as ALTRs decompress from the hip into the surrounding tissue planes; these patterns may also influence the onset and severity of patient symptoms. Questions/purposes Through a multicenter study approach, we asked: (1) Is ALTR location related to the surgical approach used for arthroplasty in patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…Screening patients with metal ion levels was not common practice until around 2010, coinciding with the time that the ASR THA (DePuy, Warsaw, IN, USA) was recalled. 5 Prior to this time, metal ion screening was only available at certain centers, but not widely available throughout the United States. Therefore, the first metal ion level that most patients have would likely be years after the MoM THA was performed after the widespread availability of the metal ion test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening patients with metal ion levels was not common practice until around 2010, coinciding with the time that the ASR THA (DePuy, Warsaw, IN, USA) was recalled. 5 Prior to this time, metal ion screening was only available at certain centers, but not widely available throughout the United States. Therefore, the first metal ion level that most patients have would likely be years after the MoM THA was performed after the widespread availability of the metal ion test.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The theoretical benefits of improved wear characteristics and the ability to utilise a larger femoral head size with the same acetabular shell have been negated by the risk of developing an adverse local tissue reaction (ALTR). 4 , 5 Secondarily, the revision rates following MoM THA have been significantly higher than those of metal on polyethylene THAs. 6 Tissue damage is likely multifactorial, but appears to be related to the release of cobalt and chromium from the implant.…”
Section: Introductionmentioning
confidence: 99%
“…With improving techniques MRI may become more sensitive . With metal‐on‐metal total hip arthroplasty (THA) and the associated major risk of adverse local tissue reactions (ALTR), MARS gained importance . But also with other types of orthopedic implants the so‐called “pseudotumors,” initiated by excessive wear, may be observed .…”
Section: Clinical Applicationmentioning
confidence: 99%
“…In the algorithmic approach to diagnosis and management of metal‐on‐metal arthroplasty published in 2012 by the hip society, imaging should include ultrasound or metal artifact reduction sequence MRI in addition to plain radiography . MARS sequences including VAT and SEMAC have been shown to be useful for detection, staging, and progression analyses of adverse local tissue reactions (ALTR) in the context of metal‐on‐metal hip prostheses . Several studies reported ALTR findings on MRI in up to a third of asymptomatic patients, and despite missing laboratory findings, there is no significant relation between MRI findings and pain or a priori risk factors, which underlines the importance of MRI .…”
Section: Clinical Applicationmentioning
confidence: 99%
“…A detailed description of the study structure and the clinical variables collected is given in a previously published study. 15 As of 31 January 2018, all patients have either completed or exited the window for the 2-year visit. Data from the enrollment, 1-year, and 2-year visits were considered for the present analyses.…”
Section: Methodsmentioning
confidence: 99%